Standardized evaluation of learning at UABC: Psycometric analysis innovation - Jorge Gustavo Gutiérrez Benítez; Luis Alan Acuña Gamboa (Universidad de Guadalajara, 2020)
The evaluation has had a strong impact on teaching, which is why learning instruments that are valid and reliable are indispensable. The Faculty of Languages of the Universidad Autónoma de Baja California does not implement a technological tool for the development of standardized tests and their psychometric analysis. Therefore, this paper analyze the implementation of standardized tests referred to a criterion, based on the Item Response Theory. The used methodology required the integration of several committees of specialists to produce instruments that guided the construction of the test, such as the curricular relevance index table, the contents justification, etc. The test quality was evaluated using an innovating development that automatically quantified the psychometric criteria of validity and trustworthiness like the difficulty index of the items and the discrimination index. The results allow to observe the quality of the test identifying the yield of each item, as well as the yield and level of knowledge of the participant students sample, which contributes to the realization of more accurate assessments of their academic performance. It is concluded that the instrument showed utility for both formative and summative evaluation.